2022
DOI: 10.1200/op.21.00119
|View full text |Cite
|
Sign up to set email alerts
|

“I'm Being Forced to Make Decisions I Have Never Had to Make Before”: Oncologists' Experiences of Caring for Seriously Ill Persons With Poor Prognoses and the Dilemmas Created by COVID-19

Abstract: PURPOSE: The COVID-19 pandemic has created a new set of problems for clinicians. This study examines the experiences of oncologists providing care to seriously ill persons near the end of life in the context of the COVID-19 pandemic. METHODS: Between January 2020 and August 2020, we conducted semistructured, in-depth individual interviews with 22 purposefully sampled oncologists from practices enrolled in the Michigan Oncology Quality Consortium. Deidentified transcripts of the interviews were examined using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 46 publications
0
18
0
1
Order By: Relevance
“…Our study, which focuses on the physician experience providing cancer care during the first COVID-19 surge, constitutes a unique contribution to the literature. Although other studies have focused on experiences providing endof-life care during COVID-19, including telemedicine barriers, 12,21 the themes identified here reflect the myriad of ways in which the COVID-19 surge affected physicians' experiences providing routine cancer care. Another strength of our study is that it was accomplished in a setting where the focus is specifically on patients with cancer.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our study, which focuses on the physician experience providing cancer care during the first COVID-19 surge, constitutes a unique contribution to the literature. Although other studies have focused on experiences providing endof-life care during COVID-19, including telemedicine barriers, 12,21 the themes identified here reflect the myriad of ways in which the COVID-19 surge affected physicians' experiences providing routine cancer care. Another strength of our study is that it was accomplished in a setting where the focus is specifically on patients with cancer.…”
Section: Discussionmentioning
confidence: 93%
“…10 However, there has been little in-depth investigation into the experiences of physicians providing cancer-specific care in a location experiencing a COVID-19 surge. Although recent studies have examined the experiences of oncologists providing end-of-life care for patients during COVID-19, 12 and burnout and stress related to disruptions in treatment, clinical research, and professional development, 9 the ways in which oncologists' experienced changes in delivery of routine cancer care, as well as the experiences of oncologic hospitalists devoted to inpatient care, has not previously been explored. In addition, this study focuses on oncologic care during the initial surge of COVID-19 at the pandemic's global epicenter.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study reveal that the clinician distress and emotional burden documented among those providing in-person care were also present among clinicians who delivered care remotely during a COVID-19 surge. 24,25 Characterizations of the provider strain induced by telemedicine is limited: a single-institution study of providers across a variety of disciplines found an association between telemedicine practice and reductions in selfdescribed burnout 26 ; however, clinicians in another study described significant concerns about the loss of in-person connection and physical touch, as well as possible increased risk for burnout. 27 Other recent studies suggest that phone, but I think that in order to improve things, I think the [face-to-face] access has to be there" (P10) • Develop and integrate a triage and tracking system to determine team members who will be in-person and virtual over time.…”
Section: Discussionmentioning
confidence: 99%
“…Some have noted the potential benefits of VC and email for enhancing equitable care [10][11][12], including increased health care utilization among racialized minorities and those with travel restrictions. Others have expressed concerns about digital divides in access to VC due to structural marginalization [13][14][15][16][17], particularly among marginalized populations known to be more prone to adverse oncologic outcomes [18,19]. These concerns underscore the importance of investigating inequities following the adoption of digital health tools and addressing their impact on oncologic care [20,21].…”
Section: Introductionmentioning
confidence: 99%